Biochemical characterization of Indian mustard (Brassica juncea L.) genotypes in response to moisture stress and irrigation modules - Sukhmaninder Kaur,; Pushp Sharma, (Journal of Oilseed Brassica, 2026)
In the current investigation, the impact of moisture stress and irrigation modules was studied on biochemicalcharacteristics in twelve Brassica juncea genotypes. Experiment was laid in split plot design with threemoisture treatments viz. only pre sowing irrigation (I0), one irrigation at 35 DAS (I1) and two irrigations, oneat 35 DAS and second at 65 DAS (I2).Water stress up-regulated the sugars and proline content in thegenotypes while it reduced the protein content. Highest amount of total sugars was recorded in K-9-108(70.3 mg g-1 DW), reducing sugars in RLC1 (12.61 mg g-1 DW), protein content in MLM-19 and NLM-3 (8.8mg g-1DW) while highest proline was in NPJ-79 (0.87mg g-1 DW) under moisture stress. Genotypes differedsignificantly for the biochemical constituents and total soluble proteins increased progressively with one andtwo irrigations.